Potential Implications of Quercetin in Autoimmune Diseases - Shen, Pan; Lin, Weiji; Deng, Xuan; Ba, Xin; Han, Liang; Chen, Zhe; Qin, Kai; Huang, Ying; Tu, Shenghao (Frontiers in Immunology, 2021)
Abstract Autoimmune diseases, a worldwide health problem with growing up rates of morbidity, are characterized by the breakdown and dysregulation of the immune system. Although the etiology and pathogenesis are still unclear, the application of dietary supplements is gradually increasing in patients with autoimmune diseases, mainly due to its positive effects, relatively safety and low-cost. Quercetin is a natural flavonoid widely presented in fruits, herbs and vegetables. It has been proved to possess a wide range of beneficial erects and biological activities, such as anti-inflammation, anti-oxidation, neuroprotection. Several studies in recent years have reported that quercetin attenuates rheumatoid arthritis, inflammatory bowel disease, multiple sclerosis, systemic lupus erythematosus in human or animal models. This review summarizes the evidences for the pharmacological potential and inhibition of quercetin on autoimmune diseases, supporting the point of view that quercetin could be applied in prevention and treatment against autoimmune diseases.